Structural analysis of prodomain inhibition of cysteine proteases in plasmodium species - Njuguna, Joyce Njoki (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
Plasmodium is a genus of parasites causing malaria, a virulent protozoan infection in humans resulting in over a million deaths annually. Treatment of malaria is increasingly limited by parasite resistance to available drugs. Hence, there is a need to identify new drug targets and authenticate antimalarial compounds that act on these targets. A relatively new therapeutic approach targets proteolytic enzymes responsible for parasite"Ÿs invasion, rupture and hemoglobin degradation at the erythrocytic stage of infection. Cysteine proteases (CPs) are essential for these crucial roles in the intraerythrocytic parasite. CPs are a diverse group of enzymes subdivided into clans and further subdivided into families. Our interest is in Clan CA, papain family C1 proteases, whose members play numerous roles in human and parasitic metabolism. These proteases are produced as zymogens having an N-terminal extension known as the prodomain which regulates the protease activity by selectively inhibiting its active site, preventing substrate access. A Clan CA protease Falcipain-2 (FP-2) of Plasmodium falciparum is a validated drug target but little is known of its orthologs in other malarial Plasmodium species. This study uses various structural bioinformatics approaches to characterise the prodomain"Ÿs regulatory effect in FP-2 and its orthologs in Plasmodium species (P. vivax, P. berghei, P. knowlesi, P. ovale, P. chabaudi and P. yoelii). This was in an effort to discover short peptides with essential residues to mimic the prodomain"Ÿs inhibition of these proteases, as potential peptidomimetic therapeutic agents. Residues in the prodomain region that spans over the active site are most likely to interact with the subsite residues inhibiting the protease. Sequence analysis revealed conservation of residues in this region of Plasmodium proteases that differed significantly in human proteases. Further prediction of the 3D structure of these proteases by homology modelling allowed visualisation of these interactions revealing differences between parasite and human proteases which will lead to significant contribution in structure based malarial inhibitor design.
Keywords: Plasmodium; Cysteine proteinases; Proteolytic enzymes; Malaria -- Chemotherapy; Antimalarials; Plasmodium falciparum